Non-invasive prenatal testing: a revolutionary journey in prenatal testing - Abedalthagafi, Malak; Bawazeer, Shahad; Fawaz, Romy I.; Heritage, A. Merrihew; Alajaji, Nouf M.; Faqeih, Eissa (Frontiers in Medicine, 2023)
Non-invasive prenatal testing (NIPT) is a pioneering technique that has consistently advanced the field of prenatal testing to detect genetic abnormalities and conditions with the aim of decreasing the incidence and prevalence of inherited conditions. NIPT remains a method of choice for common autosomal aneuploidies, mostly trisomy 21, and several monogenic disorders. The advancements in gene sequencing techniques have expanded the panel of conditions where NIPT could be offered. However, basic research on the impact of several genetic conditions lags behind the methods of detection of these sequence aberrations, and the impact of the expansion of NIPT should be carefully considered based on its utility. With interest from commercial diagnostics and a lack of regulatory oversight, there remains a need for careful validation of the predictive values of different tests offered. NIPT comes with many challenges, including ethical and economic issues. The scientific evidence, technical feasibility, and clinical benefit of NIPT need to be carefully investigated before new tests and developments are translated into clinical practice. Moreover, the implementation of panel expansion of NIPT should accompany expert genetic counseling pre- and post-testing.